Mycosands: Fungal diversity and abundance in beach sand and recreational waters - Relevance to human health - (:unkn) unknown (ELSEVIER, 2021)
The goal of most studies published on sand contaminants is to gather and discuss knowledge to avoid faecal contamination of water by run-offs and tide-retractions. Other life forms in the sand, however, are seldom studied but always pointed out as relevant. The Mycosands initiative was created to generate data on fungi in beach sands and waters, of both coastal and freshwater inland bathing sites. A team of medical mycologists and water quality specialists explored the sand culturable mycobiota of 91 bathing sites, and water of 67 of these, spanning from the Atlantic to the Eastern Mediterranean coasts, including the Italian lakes and the Adriatic, Baltic, and Black Seas. Sydney (Australia) was also included in the study. Thirteen countries took part in the initiative. The present study considered several fungal parameters (all fungi, several species of the genus Aspergillus and Candida and the genera themselves, plus other yeasts, allergenic fungi, dematiaceous fungi and dermatophytes). The study considered four variables that the team expected would influence the results of the analytical parameters, such as coast or inland location, urban and non-urban sites, period of the year, geographical proximity and type of sediment. The genera most frequently found were Aspergillus spp., Candida spp., Fusarium spp. and Cryptococcus spp. both in sand and in water. A site-blind median was found to be 89 Colony-Forming Units (CFU) of fungi per gram of sand in coastal and inland freshwaters, with variability between 0 and 6400 CFU/g. For freshwater sites, that number was 201.7 CFU/g (0, 6400 CFU/g (p = 0.01)) and for coastal sites was 76.7 CFU/g (0, 3497.5 CFU/g). For coastal waters and all waters, the median was 0 CFU/ml (0,1592 CFU/ml) and for freshwaters 6.7 (0, 310.0) CFU/ml (p < 0.001). The results advocate that beaches should be monitored for fungi for safer use and better management. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Beach; Fungi in sand; Bathing; Allergenic fungi; Bathing water; Mycosis; CANDIDA-PARAPSILOSIS COMPLEX; PATHOGENIC FUNGI; ANTIFUNGAL SUSCEPTIBILITY; CRYPTOCOCCUS-ALBIDUS; INFECTIOUS-DISEASE; FILAMENTOUS FUNGI; AIRBORNE FUNGI; MARINE FUNGI; SEA-WATER; YEASTS